Smart Vehicles, Smarter Defenses: AI's Role in SDV Cybersecurity - Premanand Narasimhan,; Dr. N. Kala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Software-Defined Vehicles (SDVs) represent a paradigm shift in the automotive industry, offering unprecedented flexibility, connectivity, and intelligence. This paper explores SDVs, elaborating on their architecture, benefits, intersection with technologies like smart cities and autonomous vehicles, cybersecurity challenges, and digital forensics methodologies for investigating cyber incidents. Finally, it examines the WP.29 regulation framework and its enforcement across nations, accompanied by detailed visualization charts.